PERENCANAAN PRODUKSI TAHU SEMEDANG PADA UMKM X - Liwun, Stephanus; Mulyanto, Tri; Larasati, Nabila (Jurnal Teknik dan Science, 2024)
MSME X is a micro, small and medium enterprise that produces Sumedang tofu distributed to several cities in Jabodetabek. The amount of tofu produced is to consumer demand. This study aims to provide alternative solutions related to production planning and propose production costs that are appropriate for each production. The method used in this research is aggregate planning chase and hybrid. The results of this study indicate that the production cost using the chase strategy method is Rp. 1,677,361,893.00. Meanwhile, the hybrid strategy method with the model I is the condition of raw material costs of Rp. 12,338.00 is Rp. 1,688,271,831.00. The hybrid strategy method with model II is raw material cost condition; IDR 13,000.00 is IDR 1,755,442,617.00. This study concludes that the method that produces the lowest cost is the chase strategy.